The Efficacy of Targeted Exercise on Gross Motor and Neuromuscular Performance in Survivors of Childhood Leukemia: A Pilot Study - Marchese, Victoria; Rock, Kelly; York, Teresa; Ruble, Kathryn; Gray, Vicki L. (Frontiers in Pediatrics, 2022)
Objectives: This quasi-experimental study examined the efficacy of targeted exercise training on gross motor performance and neuromuscular impairments in survivors of childhood acute lymphoblastic leukemia (ALL CCS). Materials and methods: Ten ALL CCS (median age: 10 years; range: 6-14 years) performed a six-week training program three times per week (five in-person sessions), including a warm-up, total body stretching, progressive jump rope training, and a cool down. Gross motor performance (test of gross motor proficiency) and lower extremity rate of muscle activation (electromyography), joint torques (motion capture and force plate), and jump height (motion capture) were measured during a countermovement jump at baseline and post-training. Results: Post-training, ALL CCS demonstrated improvements in body coordination, strength and agilty, bilateral coordination, running speed and agility, and strength gross motor performance (mean change: 1.6-8.1; p<0.05), the rate of muscle activation of the tibialis anterior and vastus lateralis muscles (mean change: 0.58-0.75; p<0.05), hip and ankle joint torques (mean change: 0.07; p<0.05), and jump height (mean change: 0.05; p<0.05). Conclusion: This study demonstrated that targeted exercise training can improve gross motor performance and neuromuscular impairments in ALL CCS post-medical treatment.